Media Pembelajaran Pendidikan Inklusi Sahabat Kecil Therapy & Learning Centre di Medang - Ika, Ika; Handayani, Alfy Dian; Febrianti, Lilis; Maemunah, Siti (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The purpose of this study is to find out the learning media used by inclusive educators in Sahabat Kecil Therapy and Learning Centre in Medang. This qualitative descriptive research involves primary informants consisting of inclusive guidance teachers and school principals. Data collection techniques include interviews, observations, and documentation. Data analysis is done through descriptive analysis. The research findings show that: 1) learning media in inclusive education at Sahabat Kecil Therapy and Learning Centre in Medang use various therapy tools or learning aids such as alphabet boards, puzzles, and sandboxes to train children's creativity, which is crucial in facilitating the learning process. 2) Learning sessions at Sahabat Kecil Therapy and Learning Centre in Medang are conducted in two sessions to facilitate the learning process. 3) Challenges faced during the inclusive learning of children at Sahabat Kecil Therapy and Learning Centre in Medang include hyperactive children, uncontrolled emotions in learning, and disrupted teacher-parent relationships. Solutions to maximize inclusion programs in schools include activating school evaluation programs, participating in inclusive service training or workshops, and forming relationships or networks of supervisors to monitor teachers' work for better and more planned programs.